Proton-conducting crystalline porous materials - Meng, Xing; Wang, Hai-Ning; Song, Shu-Yan; Zhang, Hong-Jie (Chemical Society reviews, 2017)
Crystalline porous materials are currently a hot research topic in the field of proton-conducting materials. Crystalline porous materials include metal-organic frameworks (MOFs), coordination polymers (CPs), polyoxometalates (POMs) and covalent organic frameworks (COFs). The designable structures and high surface areas of these materials provide great opportunities to orderly accommodate proton carriers and to systemically modify the concentration and mobility of proton carriers in available spaces. Based on the understanding of the relationship between the structure and proton conductivity, controllable synthesis of porous materials with high proton conductivity will gradually be achieved. This review summarizes the emerging studies of these materials and their unique proton conductivities. This review summarizes the emerging studies of proton-conducting materials, and discusses the synthetic strategies and possible mechanisms, identifying key structural factors.